晚清戊戌維新前官民對英國教育的引介初探 The Introduction of British Education in Late Ch'ing China Before 1898 - 周愚文 Yu-Wen Chou (National Taiwan Normal University, 2017)
在清光緒早期使英外交官介紹英國教育之前，19 世紀起即已有傳教士及官民編著史地書 籍介紹之，本研究據此分析其對英國教育的引介。研究發現戊戌維新前，有24種書記錄了英 國教育措施，其要點如下： 一、範圍以中小學及大學最多，少數兼及幼兒園、軍校、其他類學校及教育行政機關。 二、地區以英格蘭為主，蘇格蘭次之。 三、中小學方面，以小學為主，內容涵蓋其慈善性質、入學年齡、校數、人數、學費、 學習內容、男女分校，兼及免費及強迫。但未注意《小學教育法》公布後，形成的董事會學 校與自願學校雙元制及其影響。 四、大學方面，多介紹牛津、劍橋、愛丁堡及都柏林等老大學的分布、名稱及數量。少 數述及其學習內容、考試、學位等第及教師。但對於大學與所屬學院的關係為何、三地體制 有所不同，及19 世紀後半新興的地方級學院等問題，多未提及。 五、諸書戊戌維新前已出版，且後人曾閱讀或引用，但實際流通量與影響不易評估。 六、此期透過遊記去理解英國方式，近似比較教育「旅人故事時期」的作法。 七、因英制偏地方分權而分歧複雜，清人很難一窺全貌，諸書僅是初步、片段的介紹； 且因社會仇外，故此階段無法進行教育借入。 The aim of this study was to explore the introduction of British education in late Ch'ing China before 1898. Twenty-four historical and geographical books and traveling records written by priests, officials, and intellectuals were analyzed. The main findings were as follows. (1) The focus was on elementary and secondary schools and universities and colleges. Few authors mentioned kindergartens, military academies, other schools, or administrative authorities. (2) The educational establishments in England were focused, and some in Scotland and Ireland were introduced. (3) The nature of charity, school age, number of schools and pupils, tuition fees, curriculum, and gender limitations of elementary schools were recorded; some sources mentioned compulsory and free education. However, the formation of dual systems of board and voluntary schools after the enactment of the Elementary Education Act in 1870 was not recorded. (4) The name, location, and number of universities in Oxford, Cambridge, Edinburgh, and Dublin were introduced in most books. However, few books mentioned their curriculum, examinations, degrees, and faculty. (5) Although all the books were published and read before 1898, their concrete circulation and influence was difficult to estimate. (6) The introduction of British education during this period was similar to that of the period of traveling's tales in comparative education development. (7) Because of the complexity of British localized education, the books were unable to completely describe it. Furthermore, because an antiforeigner climate existed in China at that time, educational borrowing was unlikely.